Detrimental effects of plant compounds on a polyembryonic parasitoid are mediated through its highly polyphagous herbivore host. Issue 3 (30th July 2013) - Lampert, Evan C.; Bowers, M. Deane
Abstract Plant defensive compounds can have sometimes severe deleterious effects on both herbivores and their natural enemies. Iridoid glycosides (IGs) are defensive compounds that are well established as deterrent to several generalist herbivores and generalist predators. Trichoplusia ni Hübner (Lepidoptera: Noctuidae) is exceptional among generalist herbivores for its ability to tolerate and thrive when feeding upon IG‐producing plant species; however, it is not known whether the compounds themselves have a harmful effect on T. ni and whether the effects in turn affect its oligophagous endoparasitoid Copidosoma floridanum Ashmead (Hymenoptera: Encyrtidae). To examine these effects, a semi‐purified extract of the IG‐containing plant Plantago lanceolata L. (Plantaginaceae), containing the IGs aucubin and catalpol, was added to artificial diets at 0, 1, 5, or 10% diet dry weight. These diets were fed to both C. floridanum‐parasitized and unparasitized T. ni. Diets higher in IGs tended to be more toxic to both parasitized and unparasitized larvae: host larvae that did survive were slightly smaller and took longer to develop on higher IG diets and total clutch size and survival of the parasitoid C. floridanum were greatly reduced as the host's dietary intake of IGs increased. Only small amounts of aucubin were detected inside the T. ni hemocoel, suggesting that the negative effect of these compounds on C. floridanum is due to nutritional quality of the host being reduced rather than direct toxic effects of the compounds.